Efficacy of Calcium Pidolate Supplementation on the Growth Performance, Tibial Breaking Strength and Income over Feed Cost of Broiler Chickens - Aguilon, Loren Domondon; Purnamasari, Listya; Olarve, Joseph Penano; dela Cruz, Joseph Flores (Faculty of Animal Science, Universitas Brawijaya, 2024)
Calcium pidolate is an organic calcium source that can be used as a supplement in the diet of broiler chickens. This is an innovative new form of calcium supplementation that promotes mineral absorption in broiler chickens. This study aimed to determine the effect of calcium pidolate supplementation on the growth performance of broiler chickens. A total of 120 one-day-old Ross chicks were used in this study. The broiler chickens were randomly distributed into two treatment groups with three replicates per treatment. The two treatment groups were the control group with calcium phosphorus supplementation and treatment 2 (T2) with calcium pidolate supplementation. The evaluated growth performance parameters included body weight, body weight gain, average daily gain, average feed consumption, feed efficiency, feed conversion ratio, percent liveability, and tibia breaking strength. The income over feed and chick cost (IOFCC) was also evaluated. The results showed no significant improvement in body weight, body weight gain, average daily gain, average feed consumption, feed efficiency, or percent viability in the T2 group. However, there was a significant increase in the tibia breaking strength of the T2 group compared to that of the control group. In addition, the control group had a greater IOFCC than did the T2 group. In summary, calcium pidolate supplementation may be used as a calcium source for improving the bone strength of broiler chickens.